2013
DOI: 10.1002/jbmr.1900
|View full text |Cite
|
Sign up to set email alerts
|

A semimechanistic model of the time-course of release of PTH into plasma following administration of the calcilytic JTT-305/MK-5442 in humans

Abstract: JTT-305/MK-5442 is a calcium-sensing receptor (CaSR) allosteric antagonist being investigated for the treatment of osteoporosis. JTT-305/MK-5442 binds to CaSRs, thus preventing receptor activation by Ca 2þ . In the parathyroid gland, this results in the release of parathyroid hormone (PTH). Sharp spikes in PTH secretion followed by rapid returns to baseline are associated with bone formation, whereas sustained elevation in PTH is associated with bone resorption. We have developed a semimechanistic, nonpopulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…A pharmacokinetic/pharmacodynamic study with oral administration of JTT-305/ MK-5442 to postmenopausal women showed that endogenous PTH was secreted from two separate reservoirs, a rapid phase within minutes and a slower phase for hours by 15 to 20 mg JTT-305/MK-5442. (57) Because of these characteristics, there were no significant increases in BMD versus placebo after 6 months of treatment in a phase 2, randomized, placebo-controlled, doseranging study involving postmenopausal women with low bone mass. (58) We hypothesized that the disadvantage of JTT-305/MK-5442 with long plasma half-life due to the secretion of PTH from the second reservoir may be beneficial for ADH patients by providing long-term effect with once or twice daily administration.…”
Section: Discussionmentioning
confidence: 99%
“…A pharmacokinetic/pharmacodynamic study with oral administration of JTT-305/ MK-5442 to postmenopausal women showed that endogenous PTH was secreted from two separate reservoirs, a rapid phase within minutes and a slower phase for hours by 15 to 20 mg JTT-305/MK-5442. (57) Because of these characteristics, there were no significant increases in BMD versus placebo after 6 months of treatment in a phase 2, randomized, placebo-controlled, doseranging study involving postmenopausal women with low bone mass. (58) We hypothesized that the disadvantage of JTT-305/MK-5442 with long plasma half-life due to the secretion of PTH from the second reservoir may be beneficial for ADH patients by providing long-term effect with once or twice daily administration.…”
Section: Discussionmentioning
confidence: 99%
“…24 Comparable anabolic effects may be produced by treatment with short-acting antagonists of calcium sensing receptor, the so-called calcilytics, which induce an acute stimulation of PTH secretion by the parathyroid gland mimicking a pulsatile secretory pattern which may lead to improvement of bone mineral density (BMD) and decrease in fracture risk. 25,26 Over the recent years, there has been convincing evidence that PTH exerts extra-skeletal effects, mainly on cardiovascular system and glucose metabolism. 27–29 However, it is still unknown whether and how the pulsatile PTH secretion may influence these extra-skeletal targets.…”
Section: Physiology Of Pth Secretionmentioning
confidence: 99%
“…Allosteric modulators of this calcium-sensing receptor can affect the secretion of PTH [Trivedi et al 2008; Riccardi, 2012]. Positive calcium-sensing receptor agonists, called calcimimetics, such as cinacalcet, can reduce PTH secretion in patients with hyperparathyroidism and renal disease [Li et al 2013; Tsuruta et al 2013], whereas negative antagonists of this receptor, called calcilytics, can inhibit the receptor function thus inducing the release of a PTH pulse [Cabal et al 2013]. Therefore, these molecules may represent new targets in the treatment of osteoporosis [Fraser et al 2004; Nemeth, 2004; John et al 2011].…”
Section: Pth-related Therapiesmentioning
confidence: 99%